The Accelerating And Constraining Factors Of The Coordinated And Balanced Development Of Regions - Bochko, Vladimir Stepanovich (Economy of Regions, 2015)
In the article, the hypothesis that the modern industrial-technological process causes complication of socio-economic space and conducts to amplification its integrity, which, in turn, causes the need for the coordinated and balanced development, is proved. The process of complication of economic space is revealed as a result of number growth of communications caused by creation of the enterprises and organizations, by the change of structure of manufacture and increase of an educational level of the population. The characteristics of a new quality of economic space are given. The factors of the coordinated and balanced development of territories are allocated. The contents «a commercial combination» is shown. The necessity of transition to the system innovation thinking in conditions of becoming complicated economic space is proved. The idea of use «rebalancing of the economy « as a new vision of equation in conditions of crisis situations is offered. The conclusion is made that the result of theoretical and practical searches should become formation vital stability of development of territories, which is provided with intelligence - technological and moral - ethical level of the population, living on it.